The Lateralized Vestibular Stimulation: Effect on Mood, Cognition, and Autonomic States in Mental Disorders - Ried, A.M. Soza; Arrau, Catalina (Journal of Psychology and Psychotherapy Research, 2024)
The vestibular system in the inner ear senses the body’s movements, which is essential for regulating reflex movements and body balance at the brain stem level. Still, it is also critical in regulating high brain functions, including mental states, motivation, mood, cognition, and reasoning. This article reviews the neuro-functional effects of lateralized vestibular stimulation in three main brain areas involved in mental disorders: the parieto–insular–vestibular cortex (PIVC), the hippocampus, and the hypothalamus. We discuss its implications for the performance of high-demanding works and possible therapeutic applications in psychiatric patients.